1 Answer

  1. Jerry- Reply


    While not a rigorous proof, you could experiment with programing by calculating k_0 = sqrt(6) and k_n+1 = sqrt (6 + k_n) for successively higher values of n.

    I think that you will find it converges pretty quickly to 3.

    You can also determine the value for convergence algebraically by squaring both sides which results in k^2 = 6 + k and then solving the quadratic.

Leave a Reply

Your email address will not be published. Required fields are marked *

You can use these HTML tags and attributes <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <strike> <strong>